PRETIE-Q Spanish Version and Affective-Functional Responses to Age-Based Strength Training in Older Women: An Exploratory Study - Farias-Valenzuela, C (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Highlights: What are the main findings? The PRETIE-Q was successfully adapted into Spanish. Tolerance increased during age-based strength training in older women, while Preference remained stable; neither was linked to affective valence or perceived exertion. Age-based strength training improved functional performance in older women. What is the implication of the main finding? Assessing Preference, Tolerance, affective valence, and perceived exertion in the context of strength training provides a comprehensive understanding of affective responses, which may promote adherence to training programs. Age-based strength training reduces health risks in older women, promoting greater independence. Background: To promote exercise adherence, programs should consider not only functional effects but also a comprehensive affective response. This study analyzed the affective responses and functional performance in an age-based Block Strength Training (BST) for older women. Methods: Twenty-eight community-dwelling and Spanish-speaking older women participated in this study (age 68.39 ± 5.95 years) performed a 12-week age-based BST. Preference for and Tolerance of the Intensity of Exercise Questionnaire Spanish version (PRETIE-Q-Sv) was measured before and after each block four times. Additionally, Feeling Scale (FS) and Rating of Perceived Exertion session (sRPE) were measured. Functional performance was assessed before and after the BST using Timed Up and Go, Two-Minutes Step Test, and Five Times Stand-to-Sit Test. Statistical analyses included Cronbach’s alpha (α), Spearman’s (ρ, rho) and Pearson’s (r) coefficients, repeated-measures ANOVA or Friedman, and Paired comparison. The significance level was set at p < 0.05. Results: The PRETIE-Q-Sv showed acceptable internal consistency for both Preference (α = 0.80) and Tolerance (α = 0.78) constructs, with most items showing reliability with their construct scores (ρ ≥ 0.50). Preference remained stable (F (2.39, 64.59) = 2.64, p = 0.070, η2p = 0.09), and Tolerance increased (F (2.09, 56.35) = 11.84, p < 0.001, η2p = 0.30)., with overall average scores close to 22. These were not related to FS or sRPE (ρ/r = −0.02 to 0.14). All functional performance tests showed significant improvement after the BST (p < 0.001, d/rb > 0.80). Conclusions: The PRETIE-Q-Sv adapted well to the language. Preference and Tolerance remained at intermediate levels, with BST programming aligned to individual tendencies and showing no association with FS or sRPE, whereas the increase in Tolerance suggests that BST enhances older women’s ability to persist under uncomfortable effort. Improvements in functional performance support the effectiveness of the BST as a precision exercise dose. © 2025 by the authors.